Tārīkh-i Harāt - Mīr-Ḥusaynī, Muḥammad Hasan; Mihrīzī, Muḥammad Riḍā Abūʿī; Afshār, Īraj (Miras Maktoob, ISBN: 9789004365452., 2019)
This is a facsimile edition of a unique copy of an historical text in Persian, found in some antique shop in Yazd, Iran, several decades ago. The text is incomplete, but must have consisted of at least six chapters ( bāb ). What remains are the last part of chapter four, chapter five, and the first part of chapter six. Chapter four treats of the rulers of Khurāsān until the reign of Muʿizz al-Dīn Aḥmad Sanjar (d. 552/1157-8). Chapter five is about memorable events in Herat, while the remaining part of chapter six c0ntains a listing of the qualities of Herat and Khurāsān. The manuscript bears no title and no author is mentioned. The editors derive title and author from a reference in Muʿīn al-Dīn Isfizārī's (8th/14th cent.) Rawḍāt al-jannāt fī awṣāf madīnat Harāt . The text itself dates from the early 5th/11th, the manuscript from the 8th/14th century. Valuable as an early Persian text on Herat and Khurāsān.